Managerial economics - Hirschey, Mark (South-Western Cengage Learning, 2009)
The economic concepts presented in MANAGERIAL ECONOMICS, 12e, show students how to use common sense to understand business and solve managerial problems. This innovative text helps students develop and sharpen their economic intuition--an invaluable skill that helps students, as future managers, decide which products to produce, costs to consider, and prices to charge, as well as the best hiring policy and the most effective style of organization. With its unique integrative approach, the text presents the firm as a cohesive, unified organization and demonstrates that important business decisions are interdisciplinary. A basic valuation model is constructed and used as the underlying economic model of the firm; each topic is then related to an element of the value maximization model--a process that shows how management integrates accounting, finance, marketing, personnel, and production functions